Ethnic differences in intergenerational housing mobility in England and Wales - Franz Buscha; Emma Gorman; Patrick Sturgis; Min Zhang (Global Labor Organization (GLO), 2023)
Home ownership is the largest component of wealth for most households and its intergenerational transmission underpins the production and reproduction of economic inequalities across generations. Yet, little is currently known about ethnic differences in the intergenerational transmission of housing tenure. In this paper we use linked Census data covering 1971-2011 to document rates of intergenerational housing tenure mobility across ethnic groups in England and Wales. We find that while home ownership declined across all ethnic groups during this period, there were substantial differences between them. Black, Pakistani and Bangladeshi households experienced the strongest intergenerational link between parent and child housing tenure, and Black individuals had the highest rates of downward housing mobility. In contrast, those of Indian origin had homeownership rates similar to White British families, and a weaker link between parent and child housing tenure. These patterns are likely to exacerbate existing gradients in other dimensions of ethnicity-based inequality, now and in the future.
Keywords: J62; I24; R31; P46; 330; housing; social mobility; wealth transmission; ethnicity